2019
DOI: 10.1681/asn.2019020192
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Function and Structural Integrity Depend on Hyaluronan Synthesis by Glomerular Endothelium

Abstract: Background A glycocalyx envelope consisting of proteoglycans and adhering proteins covers endothelial cells, both the luminal and abluminal surface. We previously demonstrated that short-term loss of integrity of the luminal glycocalyx layer resulted in perturbed glomerular filtration barrier function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 37 publications
1
52
0
Order By: Relevance
“…High molecular weight HA enhances human pulmonary EC barrier function and inhibits LPS-induced pulmonary vascular leakiness [27]. Our recent study showed that endothelial specific deletion of has2 in mice leads to loss of HA incorporation in glycocalyx, causing endothelial dysfunction and vascular destabilization in multiple tissues, such as kidney, retina and heart [10]. Here, we further explored that loss of endothelial HA impaired microvascular perfusion and dysregulated angiogenesis in response to artery occlusion, which is clinically related to diabetic patients with critical limb ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…High molecular weight HA enhances human pulmonary EC barrier function and inhibits LPS-induced pulmonary vascular leakiness [27]. Our recent study showed that endothelial specific deletion of has2 in mice leads to loss of HA incorporation in glycocalyx, causing endothelial dysfunction and vascular destabilization in multiple tissues, such as kidney, retina and heart [10]. Here, we further explored that loss of endothelial HA impaired microvascular perfusion and dysregulated angiogenesis in response to artery occlusion, which is clinically related to diabetic patients with critical limb ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…14-150). Presence of introduced genes from ear pinched DNA samples is performed on all animals during breeding and for confirmation of has2 gene mutation (exon 2 deletion) after tamoxifen on Has2-cKO mice at the end of the experiment using PCR and primers, as described earlier [10]. Only Has2-cKO mice with a confirmed mutation within their has2 gene were examined further.…”
Section: Animal Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteoglycans with bound GAGs, of which heparan sulphate and hyaluronan constitute up to 90%, are the main contributors to the function and structure of the endothelial glycocalyx ( Reitsma et al., 2007 ; Slater et al., 2012 ; Garsen et al., 2014 ; Dane et al., 2015 ). In DN and FSGS, the endothelial glycocalyx is reduced, characterized by a loss of essential GAGs, including heparan sulphate and hyaluronan, and reduced thickness ( Nieuwdorp et al., 2006a ; Kuwabara et al., 2010 ; Satoh et al., 2010 ; van den Berg et al., 2019 ). Environmental factors, such as elevated levels of glucose, oxidative stress, or inflammatory stimuli, can modulate the endothelial glycocalyx ( Singh et al., 2011 ; Singh et al., 2013 ; Kolarova et al., 2014 ).…”
Section: Genc Dysfunction In Dn and Fsgsmentioning
confidence: 99%